Access to Latrine Facilities and Associated Factors in India: An Empirical and Spatial Analysis. Issue 3 (December 2022) - Mondal, Dinabandhu
Access to adequate sanitation facilities is a basic human right and fundamental to good health. Inadequate and unhygienic sanitation practices have severe consequences for public health and socio-economic development. This study examines the levels and trends in access to latrine facilities, spatial variations and the associated socio-economic factors in India. Data drawn from the National Sample Survey Organization's (NSSO) 69th (2012) and 76th rounds (2018) were used in this study. Moran's 'I' statistic and Local Indicators of Spatial Association (LISA) were applied to assess the spatial variations in access to latrine facilities. Bivariate and multivariate logistic regressions were employed to examine the factors associated with latrine use. The findings revealed that access to sanitation facilities is unsatisfactory, and there is a huge rural–urban gap in latrine use. Unequal access among socio-economic groups is also very prominent. The study found substantial geographical variations in latrine use across the country; open defecation is highly prevalent in eastern and central regions of the country, while the north and north-eastern regions have better access to latrine facilities. Factors like education, occupation, socio-religious affiliation, water availability, and economic status are significant determinants of accessibility to latrine. It is recommended that targeted interventions for the socio-economically disadvantaged groups, spreading awareness about the importance of latrine use and hygienic practices, and proper assistance for construction and maintenance of toilets could be helpful to combat the harmful practice of open defecation and ensure adequate and equitable sanitation for all.